2007
DOI: 10.1097/hjh.0b013e3280a8b87d
|View full text |Cite
|
Sign up to set email alerts
|

Function and regulation of epithelial sodium transporters in the kidney of a salt-sensitive hypertensive rat model

Abstract: NCC and possibly NKCC2, but not ENaC, were functionally upregulated in the kidneys of rats subjected to sensory nerve degeneration plus high salt intake, suggesting that sensory neurotransmitters may regulate the expression of the former but not the latter, which may underlie the development of salt-sensitive hypertension in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…These data show that selective knockdown of neuronal TRPV1 enhances prohypertensive effects induced by salt loading and that pressor effects of TRPV1 shRNA may be mediated, at least in part, by enhancement of the sympatho-excitatory response. We have previously shown that neonatal degeneration of TRPV1-expressing sensory nerves increased salt sensitivity of arterial pressure as these rats grew into adulthood [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . However, the systemic sensory denervation used in these previous studies precluded us from making conclusions about whether the observed effect was due to the removal of TRPV1 or other proteins co-expressed in the same nerves innervating any specific organs or tissues [21,22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data show that selective knockdown of neuronal TRPV1 enhances prohypertensive effects induced by salt loading and that pressor effects of TRPV1 shRNA may be mediated, at least in part, by enhancement of the sympatho-excitatory response. We have previously shown that neonatal degeneration of TRPV1-expressing sensory nerves increased salt sensitivity of arterial pressure as these rats grew into adulthood [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . However, the systemic sensory denervation used in these previous studies precluded us from making conclusions about whether the observed effect was due to the removal of TRPV1 or other proteins co-expressed in the same nerves innervating any specific organs or tissues [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, defining the role of TRPV1-positive sensory nerves in the regulation of blood pressure and salt sensitivity will be useful. We have shown previously that the degeneration of TRPV1-expressing sensory nerves throughout the neonatal body by subcutaneous injection of capsaicin, a selective TRPV1 agonist, leads to increased salt sensitivity of arterial pressure, indicating that TRPV1-positive sensory nerves play a counter-regulatory role against salt-induced increases in blood pressure [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . The underlying mechanism of anti-hypertensive effects of TRPV1 may involve its counter-balancing role against the activation of the renin-angiotensin-aldosterone system [7][8][9] , sympathetic nervous system [10] , endothelin system [11,12] , superoxide generation system [13,14] , and epithelial sodium transporters [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous systems can influence BP over the short term, long-term BP regulation depends on the renal excretion of sodium (22). An increased BP in response to dietary sodium (salt sensitivity) has been widely reported in humans and animals and is proposed as a major factor in the pathogenesis of hypertension (4).…”
mentioning
confidence: 99%
“…Salt-induced NHE3 suppression is more impaired in Dahl salt-sensitive rats than in Dahl salt-resistant rats (68). NKCC2 activity in thick ascending limb is also upregulated in salt-sensitive rats (3,10,66). Single-nucleotide polymorphisms involving NKCC2 activation in thick ascending limb are associated with salt-sensitive hypertension in humans (123).…”
Section: Animal Models Of Salt-sensitive Hypertensionmentioning
confidence: 99%
“…The last fraction is reabsorbed via epithelial Na ϩ channels (ENaC) in the CNT/CD. Na ϩ /H ϩ exchanger (NHE)3 in proximal tubules (62,68) and NKCC2 in the thick ascending limb (3,10,66) are associated with salt-sensitive hypertension in animal models. Salt-induced NHE3 suppression is more impaired in Dahl salt-sensitive rats than in Dahl salt-resistant rats (68).…”
Section: Animal Models Of Salt-sensitive Hypertensionmentioning
confidence: 99%